The Discursive Construction of Teachers’ Desirable Identity on a Social Networking Site - Radzuwan, Ab Rashid; Nor Jijidiana, Azmi; Safawati Basirah, Zaid (2016)
This study is situated in the broader identity-construction literature. Bringing discourse community theory to examine teachers’ postings on Facebook Timelines, we explored how teachers discursively construct socially desirable identities to fit into the Timeline community. Data were gathered from the Status updates and Comments on 29 Timelines belonged to Malaysian English language teachers who were purposively chosen as they often posted and commented on teaching-related issues on their Timelines. The analysis shows that the commonest form of identity construction on the teachers’ Timelines was as an engager which had been carefully constructed to portray positive self-image. This paper concludes that when participating on a public networking site, the teachers were being strategic as not to construct identities which could tarnish their professional image.